Verrucous Carcinoma in External Auditory Canal A Rare Case (Delta Medical College Journal, 2013)
Verrucous carcinoma is a variant of squamous cell carcinoma. It is of low grade malignancy and rarely present with distant metastasis. Oral cavity is the commonest site of this tumour, other sites are larynx, oesophagus and genitalia. Verrucous carcinoma in external auditory canal is extremely rare. This is the presentation of a 45 years old woman who came to the ENT & Head Neck Surgery department of Delta medical college, Dhaka, Bangladesh with discharging left ear and impairment of hearing on the same side for 7 years. Otoscopic examination showed a mass occupying almost whole of the external auditory canal and the overlying skin was thickened, papillary and blackish. Cytology from external auditory canal scrap showed hyperkeratosis and parakeratosis. External auditory canal bone was found eroded at some parts. Excision of the mass was done under microscope. Split thickness skin grafting was done in external auditory canal. The mass was diagnosed as verrucous carcinoma on histopathological examination. Afterwards she was given radiotherapy. Six months follow up showed no recurrence and healthy epithelialization of external auditory canal.DOI: http://dx.doi.org/10.3329/dmcj.v1i1.14973 Delta Med Col J. Jan 2013;1(1):25-27